1980
DOI: 10.1002/lary.1980.90.6.962
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Perceptual Problems in Children: Considerations for the Otolaryngologist and Audiologist

Abstract: Five cases of children with auditory processing problems are presented. These children had essentially normal peripheral hearing and ENT exam, but were referred with a question of hearing loss. An auditory perceptual test battery including rapidly alternating speech (RASP), binaural fusion, low pass filtered speech (LPFS), competing sentences, staggered spondiac words (SSW), dichotic digits and frequency patterns was employed. Though some of these tests did not show a perceptual deficit, the majority did depic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

1984
1984
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 10 publications
0
8
0
4
Order By: Relevance
“…Our observation of the ADP in LD children is not a recent or exclusive finding. In their study of LD children, Musiek and Geurkink (1980) alluded to the components of the ADP in several cases with strikingly similar findings. Pinheiro (1977) reported similar results in a number of LD children.…”
Section: Central Auditory Test Findingsmentioning
confidence: 81%
“…Our observation of the ADP in LD children is not a recent or exclusive finding. In their study of LD children, Musiek and Geurkink (1980) alluded to the components of the ADP in several cases with strikingly similar findings. Pinheiro (1977) reported similar results in a number of LD children.…”
Section: Central Auditory Test Findingsmentioning
confidence: 81%
“…The present study is unique, however, in that a test battery approach was utilized including monotic and nonspeech measures, as well as dichotic measures utilizing sentence information which are less likely t o be affected by peripheral hearing loss. Due to the likelihood that central auditory processing disorders are heterogeneous, there is general agreement that a test battery approach is preferable to a single measure for quantifying central auditory function (Musiek & Geurkink, 1980;Pinheiro, 1977b;Stecker, 1992;Willeford, 1977). Auditory duration and pitch pattern measures employ similar paradigms and response demands; however, overall performance among AD subjects on the duration pattern test (51.2%) was substantially lower than that for pitch pattern sequencing (66.2%).…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, other authors (21,22) compared different forms to answer (verbal, motor and humming) while analyzing the performance of children with disorder of normal learning. They found that the children were able to perform humming, but they presented great difficulty while answering orally or manually, unlike the children who were considered normal, which showed little or no difference in response.…”
Section: Discussionmentioning
confidence: 99%